Association of Systemic Inflammation and Malnutrition With Survival in Nasopharyngeal Carcinoma Undergoing Chemoradiotherapy: Results From a Multicenter Cohort Study - Wang, Xin; Yang, Ming; Ge, Yizhong; Tang, Meng; Rao, Benqiang; Chen, Yongbing; Xu, Hongxia; Cong, Minghua; Guo, Zengqing; Shi, Hanping (Frontiers in Oncology, 2021)
Background: Malnutrition and systemic inflammation are common in patients with Nasopharyngeal Carcinoma (NPC). The PGSGA score and Neutrophil-to-Lymphocyte ratio (NLR) reﬂect the integrated nutritional status and inflammatory level of patients with NPC, respectively. We performed this paper to identify whether NLR and PGSGA score are associated with outcome and survival time for patients with NPC undergoing chemoradiotherapy. Methods: The multicentre cohort study included 1102 patients with NPC between June 2012 and December 2019. The associations of all-cause mortality with NLR and PGSGA score were calculated using the Kaplan-Meier method and the log-rank test. We also did a multivariate-adjusted Cox regression analysis to identify the independent significance of different parameters. Restricted cubic spline regression was carried out to evaluate the association between NLR and Overall survival (OS). A nomogram was established using the independent prognostic variables. Interaction terms were used to investigate whether there was an interactive association between NLR and PGSGA. Results: Total 923 patients with NPC undergoing chemoradiotherapy were included in this study, 672(72.8%) were males and 251(27.2%) were females with a mean age of 49.3±11.5 years. The Kaplan-Meier curves revealed that patients with malnutrition (PG-SGA score >3) had a worse survival than patients who were in the well-nourished group (PG-SGA score≤3) (P<0.0001). In addition, patients in the high NLR group (NLR≥3) had worse survival than those in the low NLR group (NLR<3) (P<0.0001). Patients with high PGSGA and high NLR had the worst survival(P<0.0001). An increase in NLR had an inverted L-shaped dose-response association with all-cause mortality. A nomogram was developed by incorporating domains of NLR and PGSGA score to accurately predict OS 12-60 month for patients (The C-index for OS prediction of nomogram was 0.75 (95% CI, 0.70-0.80). The interaction of PGSGA with NLR was significant (P=0.009). Patients with high PGSGA and high NLR had a nearly 4.5-fold increased risk of death (HR = 4.43, 95% CI = 2.60-7.56) compared with patients with low PGSGA and low NLR. Conclusions: Our study provided clear evidence that high PGSGA score and high NLR adversely and interactively affects the OS of patients with NPC undergoing chemoradiotherapy.